Les usages de l’altérité - Lucile Lebrette (Terrains/Théories)
The Italian-French border is a space where a selection is made between desired travellers and "undesirables". Basing their controls on a stereotypical perception of the "migrant", the police participate in the process of othering the figure of the exile. The exiles are then homogenised under a category that reduces them to a race, a social class and a criminal figure. Nevertheless, the otherness imposed at the border is not only the result of an undergone stigmatization: it also represents the source from which a whole migratory agency is deployed, allowing the exiles to displace social boundaries and to cross the territorial border. This article therefore aims to understand the migratory tactics of counter-othering, through the prism of a particular field of observation: the "breakfast" of the Kesha Niya collective. Located a few metres from the PAF (Border Police) on the Italian side, the breakfast is a place that welcomes the exiles who have just been sent back to Italy. It has become an essential stopover in the local landscape and is a particularly rich field of observation for studying the strategies of reconfiguration of social relations of otherness between exiles and activists - a reconfiguration that paves the way for border crossings.